Solusi Pendidikan Agama Islam Mengatasi Kenakalan Remaja Pada Keluarga Broken Home - Mizanul Hasanah; Muhammad Anas Maarif (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Starting from the writer's anxiety with the spread of violence and social deviation as well as the social behavior of the future young generation today. Several factors that really stand out are the result of internal influences, namely family. Most children in their teens show signs of deviance and rebellion, whether overt or secretly. The author is well aware that many other factors influence these things. However, juvenile delinquency treatment is often found due to the broken home factor. In this case, the family has an important role in creating children who have good morals in the future. One of them is by instilling good values in children, namely with Islamic religious education from an early age and ever since childhood. The approach used is descriptive qualitative with the interview method. Informants are the parents or guardians of the student. The purpose of this paper is to find out how parents teach religious education, what are the supporting and inhibiting factors of Islamic religious education and the best solutions in Islamic religious education in broken home families